Health information systems evaluation frameworks: A systematic review. (January 2017) - Eslami Andargoli, Amirhossein; Scheepers, Helana; Rajendran, Diana; Sohal, Amrik
Highlights: The paper presents a contextual approach to analyse studies on the evaluation of health information systems (HISs) by applying a content, context and process (CCP) framework. The study shows the role of context has been largely neglected in HISs evaluations. The lack of a proper method in stakeholder identification was identified. The findings highlight the need for a more complete framework to address all aspects of HISs evaluations. Abstract: Background: Evaluation of health information systems (HISs) is complicated because of the complex nature of the health care domain. Various studies have proposed different frameworks to reduce the complexity in the assessment of these systems. The aim of these frameworks is to provide a set of guidelines for the evaluation of the adequacy of health care information systems. Objective: This paper aims to analyse studies on the evaluation of HISs by applying a content, context and process (CCP) framework to address the 'who', 'what', 'how', 'when', and 'why' of the evaluation processes used. This will allow for a better understanding of the relative strengths and weaknesses of various HISs evaluation frameworks, and will pave the way for developing a more complete framework for HISs. Method: A systematic literature review on HIS evaluation studies was undertaken to identify the currently available HIS evaluation frameworks. Five academic databases were selected to conduct this systematic literature review. Results: Most of the studies only address some, but not all, of the five main questions, i.e. the who, what, how, when, why, and that there was a lack of consensus in the way these questions were addressed. The critical role of context was also largely neglected in these studies. Conclusions: Evaluation of HISs is complex. The health care domain is highly context sensitive and in order to have a complete assessment of HISs, consideration of contextual factors is necessary. Specifically, to have the right set of criteria to measure the 'what', the answer to the 'who' of the evaluation is necessary.